Laparoscopic management of vesicouterine fistula following vaginal delivery and caesarean section in the past medical history: a case report - Ordon, Wojciech; Antosiak, Beata; Pawłowicz, Paweł; Cieślak, Jarosław; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
Authors report a case of a vesicouterine fistula of a 38–year-old patient. The disease presented on the second day after physiological delivery in very early puerperium, the patient complains of urinary leakage from vagina. In the past medical history, the patient had a caesarean section 4 years ago. Laparoscopy was performed to close the fistula three months after the delivery. The bladder wall was prepared and mobilized from the vesico-utero space. The fistula was closed by single stitches. We achieved complete closing of the vesicouterine fistula and fistula symptoms were gone. Delayed laparoscopy was the proper operation to repair the vesicouterine fistula. Use of laparoscopy techniques in operating genitourinary fistulas gives very satisfactory results. In the literature, laparoscopy vesicouterine fistula closure is presented as a safe intraperitoneal surgery that is less invasive than traditional. In the authors’ view, laparoscopy is a successful and very safe method of closure of vesicouterine fistulas.